Komunikasi Politik Digital di Indonesia - Farid Nofiard (UIN Antasari Banjarmasin, 2022)
The habits of the Indonesian people in seeking the information at this time have experienced a shift from what was previously considered television and print media as a means of actual information, turning to digital media as the main media for seeking information. This is in line with the demands of the industrial revolution 4.0 which demands an all-digital society, the great attention of the Indonesian people to the internet is an opportunity for political actors to turn to digital media as a means of political communication. Through research using descriptive literature study methods, researchers try to observe through online news, scientific magazines, television news, and digital literacy related to political communication built by political actors in Indonesia today. It was found that the results of political communication built through digital media were more effective because political messages were more easily conveyed thanks to the great attention of the Indonesian people to the internet. In addition, digital media can save time and cost in delivering political messages. This digital political communication, apart from personal branding, can also be used to resolve conflicts between the government and society